Comprehensive analysis of naturally occurring radionuclides in well water: Isotopic ratios, mitigation, and dose assessment - Francisco Piñero-García; Rimon Thomas; Eva Forssell-Aronsson; Mats Isaksson (Ecotoxicology and Environmental Safety)
In Sweden, around 20 % of the potable water comes from groundwater sources and about one million people drink water from their private wells. In areas with moderate or high abundance of naturally occurring radionuclides in the bedrock, the groundwater could be enhanced with radio and chemically toxic elements such as uranium, radium, lead and polonium. Therefore, this study aims to carry out a comprehensive analysis of the behaviour and radiological impact of naturally occurring radionuclides in well water. For that, a well water survey was done in 2020 along Sweden, focusing the study on the determination of 210Po, 210Pb, 226Ra, 228Ra, 238U and 234U by alpha spectrometry. The results of the present study showed that the naturally occurring radionuclides distributions in the well water investigated were highly variable. In addition, the radionuclides with the highest contribution to the indicative dose were 210Pb > 228Ra > 210Po > 226Ra > 234U > 238U. On the other hand, the filtration and aeration purification treatment could help to remediate the radiological impact. However, the dose assessment results point out the need to include well water in the framework of the current regulations of requirements for the protection of the health of the public regarding radioactive substances in water intended for human consumption, to guarantee the quality of water from the radiological point of view.